The immigration law as a right: History of normative asymmetry - Oliván, Fernando (2019)
The purpose of this text is to analyze the importance of rights of aliens, taking as a guiding thread a historical journey. From an etymological starting point, necessary to know the nexus and origin of the present risks, we analyze the current interconnections and their relations, namely the globalization of migratory processes. The origins, causes and effects of a global citizenship, which is articulated based on a normative asymmetry, are analyzed in a substantive way. Inevitably, this reality leads towards the construction of a new social architecture, remotely controlled by supranational organisms at the service of particular interests.